Viscous-Resistance Calculation and Verification of Remotely Operated Inspection Submarine - Ardi Nugroho Yulianto; I Ketut Suastika; Aries Sulisetyono (Institut Teknologi Sepuluh Nopember, 2014)
The purpose of the present study is to calculate and verify the viscous resistance of a remotely operated inspection submarine which is used for the purpose of underwater inspections.The focus of the study is to investigate the effect of a vertical fin on the total value of the viscous resistance. In the design of a submarine, determination of the viscous resistance plays an important role. The smaller the viscous resistance, the smaller is the engine power to be required, which results in a more economic vehicle during the operation. Viscous resistance calculationswere done by computational fluid dynamics (CFD) and verifications by wind tunnel experiments. Three models of submarines were simulated and tested. Results of data analysis show that the effect of an installation of a vertical fin on the total viscous resistance is not detectable in the current experimental setting. Furthermore, comparisons between simulation and experimental results show that the root mean square errors (RMSE) are, respectively, 2.48 x 10-3, 3.18 x 10-3 and 2.88 x 10-3 for model I, II and III.